The role of starting knee angle in squat jump force-velocity profiles: interactions with subjects` strength levels and imputed push-off distance - Qin, X.; Liu, B.; Tang, R.; Liu, Y.; García-Ramos, A. (Frontiers in Physiology, 2025)
Introduction: This study investigated whether differences in the force-velocity (F-v) profile obtained using Samozino`s method during squat jumps (SJ) performed at varying knee angles are influenced by subjects` strength levels and the push-off distance (HpO) used in the analysis.